DIRECTING THE YOUTH TOWARDS CHOOSING THE RIGHT PROFESSION AND IMPROVING THE QUALITY OF LIFE: SOCIO-PSYCHOLOGICAL FACTORS (American Journal of Interdisciplinary Research and Development, 2024)
This article presents the theoretical study of psychology, the importance of professional interests in the psychological study of young people. In the study of the predisposition of students to the profession and their orientation to the profession, information is given about the role of a psychologist of secondary institutions and the tasks that are carried out in the selection of a profession.